Readmission risk and metabolic, biochemical, haematological and clinical indicators of severity in hyperemesis gravidarum - Tan, P.C.; Jacob, R.; Quek, K.F.; Omar, Siti Zawiah (Wiley, 2006)
In a retrospective analysis of 192 cases of presumed hyperemesis gravidarum, there were no biochemical markers that predicted hospital readmission. There was, however, statistically significant negative predictive value in abnormal liver function tests. This could represent acute self-limited illness with a component of hepatitis as the cause for the clinical presentation, rather than hyperemesis.